Studies in the mechanism of the gasification of carbon in pulsed blast producer - Cruz, Ibarra E.
Evidence of the feasibility of the pulsed gasificationprocess and its attendant advantages over the conventional method of gasifying with a steady blast, is provided by: (i) theoretical thermodynamic and kinetic studies aided by a critical appraisal of previous work on combustion and gasification reactions; (ii) proving experiments on the atmospheric gasification of coke.